2014
DOI: 10.1002/ar.22897
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine Enhances the Antineoplastic Activity of Gemcitabine in Pancreatic Cancer Cells by Activating Transforming Growth Factor‐β/Smad Signaling

Abstract: Drug-resistance to gemcitabine chemotherapy in pancreatic cancer is still an unsolved problem. Combinations of other chemotherapy drugs with gemcitabine have been shown to increase the efficacy of gemcitabine-based treatment. In this study, the effect of berbamine on the antitumor activity of gemcitabine was evaluated in human pancreatic cancer cell lines Bxpc-3 and Panc-1, and the underlying mechanisms were explored. Our results demonstrated that berbamine exhibited a time-and dose-dependent inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Therefore, this study observed the nucleus morphology of the SMMC-7721 cells, and the nucleus illustrated as fragmentary and polymorphonuclear in 20, 40 µmol/l berbamine treatment, which suggests that the classical apoptotic morphology was appeared in the berbamine treatment cells. Meanwhile, the apoptosis rate was also evaluated by using the flow cytometry assay, and results revealed that berbamine at concentration of 20 and 40 µmol/l significantly induced apoptosis compared to the control group, which suggests that berbamine processes the function of anti-apoptosis in SMMC-7721 cells, and is consistent with previous study ( 19 , 27 ).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, this study observed the nucleus morphology of the SMMC-7721 cells, and the nucleus illustrated as fragmentary and polymorphonuclear in 20, 40 µmol/l berbamine treatment, which suggests that the classical apoptotic morphology was appeared in the berbamine treatment cells. Meanwhile, the apoptosis rate was also evaluated by using the flow cytometry assay, and results revealed that berbamine at concentration of 20 and 40 µmol/l significantly induced apoptosis compared to the control group, which suggests that berbamine processes the function of anti-apoptosis in SMMC-7721 cells, and is consistent with previous study ( 19 , 27 ).…”
Section: Discussionsupporting
confidence: 87%
“…In HepG2, PLC/PRF/5, SK-Hep-1, and SNU398 cells, berbamine plays a role in blocking the Ca 2+ channel through inhibition of Ca 2+ /calmodulin-dependent protein kinase II (introduction). In Bxpc-3 and Panc-1 human pancreatic cancer cell lines, berbamine can enhance antitumor activity of gemcitabine through activating the TGF-β/Smad pathway (75). A derivative of berbamine is reported to induce apoptosis of A2058, A375, G361, SK-MEL-28, and SK-MEL-5 human melanoma cell lines via inhibition of the jak2/STAT3 signaling pathway (76).…”
Section: Berbamine and Its Structural Analoguesmentioning
confidence: 99%
“…Previous studies have demonstrated that the antitumor effects of BBM in a variety of tumors, including breast cancer [19], myeloma [7,20], hepatoma [9,21], prostatic neoplasms [9], pancreatic carcinoma [22] and lung cancer [23]. Jin [22] con rmed that BBM signi cantly downregulated the expression of the antiapoptotic proteins such as Bcl-2 and Bcl-xL and inhibited proliferation in pancreatic carcinoma cells. Du [24] found that BBM induced cell apoptosis and inhibited the cell proliferation through the PI3K/Akt pathway in lymphoma, the expressions of PI3K and p-Akt/Akt were down-regulated.…”
Section: Discussionmentioning
confidence: 98%